Globular cluster formation and evolution in the context of cosmological galaxy assembly: open questions. (14th February 2018) - Forbes, Duncan A.; Bastian, Nate; Gieles, Mark; Crain, Robert A.; Kruijssen, J. M. Diederik; Larsen, Søren S.; Ploeckinger, Sylvia; Agertz, Oscar; Trenti, Michele; Ferguson, Annette M. N.; Pfeffer, Joel; Gnedin, Oleg Y.
Abstract : We discuss some of the key open questions regarding the formation and evolution of globular clusters (GCs) during galaxy formation and assembly within a cosmological framework. The current state of the art for both observations and simulations is described, and we briefly mention directions for future research. The oldest GCs have ages greater than or equal to 12.5 Gyr and formed around the time of reionization. Resolved colour-magnitude diagrams of Milky Way GCs and direct imaging of lensed proto-GCs at z ∼6 with the James Webb Space Telescope (JWST) promise further insight. GCs are known to host multiple populations of stars with variations in their chemical abundances. Recently, such multiple populations have been detected in ∼2 Gyr old compact, massive star clusters. This suggests a common, single pathway for the formation of GCs at high and low redshift. The shape of the initial mass function for GCs remains unknown; however, for massive galaxies a power-law mass function is favoured. Significant progress has been made recently modelling GC formation in the context of galaxy formation, with success in reproducing many of the observed GC-galaxy scaling relations.